Archéologie de l’oeuvre Net art : une esthétique du fragment - Fourmentraux, Jean-Paul (RACAR : Revue d'art canadienne / Canadian Art Review)

(untitled) (UAAC-AAUC (University Art Association of Canada | Association d'art des universités du Canada), 2006)
When applied to the Net, art seeks to distribute the conception of interactive systems but also to produce forms of communication and exhibition involving web surfers in the process of the artwork. Websites, home pages, online workshops, list serves, and discussion forums are the frames and territories of new forms of social interaction. On the one hand, Net artists create spaces they inhabit and enrich through the accumulation of data whose goal is to form a more or less “living” archive. On the other hand, these artists use servers, access ports, and addresses to configure a world to be experienced and lived from within, inviting web surfers to temporarily inhabit this space. By joining an aesthetic of computer codes with interface design and archival art, Net art encourages various fragments both competing and coordinated – “programs,” “interfaces,” and “images” – whose status and use I propose to redefine. In other words, through the process of distributed construction of editorial content and the interpretive practices that bring it up to date, this essay examines the systems (frameworks, interfaces) and concrete forms of this digital social interaction (contracts, rituals).